First rebbachisaurid sauropod dinosaur from Asia. - Alexander Averianov; Hans-Dieter Sues (PLoS ONE, 2021)
Dzharatitanis kingi gen. et sp. nov. is based on an isolated anterior caudal vertebra (USNM 538127) from the Upper Cretaceous (Turonian) Bissekty Formation at Dzharakuduk, Uzbekistan. Phylogenetic analysis places the new taxon within the diplodocoid clade Rebbachisauridae. This is the first rebbachisaurid reported from Asia and one of the youngest rebbachisaurids in the known fossil record. The caudal is characterized by a slightly opisthocoelous centrum, 'wing-like' transverse processes with large but shallow PRCDF and POCDF, and the absence of a hyposphenal ridge and of TPRL and TPOL. The neural spine has high SPRL, SPDL, SPOL, and POSL and is pneumatized. The apex of neural spine is transversely expanded and bears triangular lateral processes. The new taxon shares with Demandasaurus and the Wessex rebbachisaurid a high SPDL on the lateral side of the neural spine, separated from SPRL and SPOL. This possibly suggests derivation of Dzharatitanis from European rebbachisaurids. This is the second sauropod group identified in the assemblage of non-avian dinosaurs from the Bissekty Formation, in addition to a previously identified indeterminate titanosaurian.